Multitasking Behavior and Perceptions of Academic Performance in University Business Students in Mexico during the COVID-19 Pandemic - Gonzáles-Gutierrez, Victoria (2022)
“The current study measures the influence of multitasking behavior and self-efficacy for self-regulated learning (SESRL) on perceptions of academic performance and views in university students during the COVID-19 pandemic in Mexico. 264 university students fulfilled an online questionnaire. It was observed that multitasking behavior negatively influences SESRL (−0.203), while SESRL showed a positive influence of 0.537 on perceptions of academic performance, and multitasking behavior had an influence of −0.097 on the perception of academic performance. Cronbach’s alpha and Average Variance Extracted values were 0.809 and 0.577 (multitasking behavior), 0.819 and 0.626 (SESRL), 0.873 and 0.725 (perceptions of academic performance), respectively. The results of the bootstrapping test showed that the path coefficients were significant. The study outcomes can support new plans in universities to ensure the best academic outcomes. Our study showed evidence of the COVID-19 impact on education behavior. This study’s novelty is based on using the partial least square structural equation modeling (PLS-SEM) technique to evaluate these variables“